Back Cover: Efficient Color‐Tunable Copper(I) Complexes and Their Applications in Solution‐Processed Organic Light‐Emitting Diodes (Chem. Asian J. 13/2017). Issue 13 (19th June 2017) - So, Gary Kwok‐Ming; Cheng, Gang; Wang, Jian; Chang, Xiaoyong; Kwok, Chi‐Chung; Zhang, Hongxing; Che, Chi‐Ming
Abstract : The emission color of dppnc‐ and neocuproine‐based Cu(I) complexes (dppnc=7, 8‐bis(diphenylphosphino)‐7, 8‐dicarba‐ nido ‐undecaborate) are tuned from green to deep red via rational modification of the neocuproine ligand structure. An external quantum efficiency (EQE) of 15.2 % and a current efficiency of 48.2 cd A −1 at 1000 cd m −2 are achieved in the solution‐processed green‐emitting device with Cu(dppnc)‐G. A maximum EQE of 10.2 %, CIE coordinates of (0.61, 0.38), and a maximum emission peak of 631 nm are achieved in the solution‐processed red‐emitting device based on Cu(dppnc)‐R. More information can be found in the Full Paper by Gang Cheng, Chi‐Ming Che et al. onpage 1490 in Issue 13, 2017 (DOI:10.1002/asia.201700081 ).